Penanggulangan Bencana Banjir di Desa Bahu Kecamatan Taliabu Selatan Kabupaten Pulau Taliabu - Yanwarin, Wilhelmina; Sindua, Nixon Jefres; Ramadhan, Muhamad Isa (Jurnal Social Science, 2024)
This research focuses on handling flood disasters, the role of the government and BPBD in handling them, and the role of the community in handling them. The research method used is qualitative. Data collection techniques include observation, interviews, and documentation, while data analysis includes reduction, display, and verification. The research results show that the Regional Disaster Management Agency (BPBD) plays an important role in overcoming the risk of flood disasters in Bahu Village. The role of this institution includes handling disasters quickly and appropriately, coordinating with related agencies, and supporting each other. Cooperation between the government and the community is well established, and the community participates in education and outreach to create early awareness. The role of the community is very important in handling flood disasters because the community is the victim and must cooperate well with the government and related agencies in emergency response and prevention. Good cooperation will equip the community with knowledge about dealing with floods so that they can anticipate and overcome disasters that threaten people's lives.